Mengenal Bentuk Geometri Melalui Kegiatan Bermain Balok Pada Anak Kelompok B Di Tk Belimbing Raya Kepahiang - Sintia, Ledia; Sari, Rika Partika; Haryaono, Mimpira (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
the purpose of this study are: To analyze the shape of geometry through block games in Group B children at Belimbing Raya Kindergarten Kepahiang. this research is a qualitative approach. The subject of this research is 5 teachers of Belimbing Raya Kindergarten Kepahiang.The method used in this research is descriptive method. Qualitative data analysis is the process of systematically searching and compiling data obtained from interviews, field notes and other materials so that it is easy to understand and of course can be informed to others. Data analysis techniques used in this study are Interactive models. introduction of geometric shapes. Most of the children of PAUD Belimbing Raya have been able to distinguish the shape of a triangle although there are still some children who have not been able to mention the shape of a triangle.